SELECTION OF MARKETING STRATEGIES THROUGH ONLINE MARKETING PLATFORMS FOR MSMES - Gordius Ago; Bayu Bayu; Trie Hierdawati; Imam Prawiranegara Gani; Ni Luh Ketut Ayu Sudha Sucandrawati (SEAN Institute, 2023)
Online marketing is one of the most common ways MSMEs to improve sales of their products or services in the current digital era. Choosing the appropriate marketing approach through online platforms can aid MSMEs in expanding their customer reach, enhancing their contact with consumers, and enhancing their client loyalty. However, MSMEs must also select the most effective marketing plan to promote sales of their products or services. SMEs frequently struggle to increase sales and expand their businesses, but this challenge may be addressed with the correct marketing approach. This research was undertaken with the objective of examining the selection of marketing strategies for micro, small, and medium-sized enterprises (MSMEs) that utilize online platforms in the marketing process to facilitate sales transactions. The research method employs a qualitative approach based on a literature review. The research results are presented in the form of a study about online platforms that are appropriate for MSMEs, as well as decisions that MSMEs can make when evaluating various marketing strategies, knowing the best way to attract consumer attention, and identifying the most effective online platform for MSMEs.